(untitled) (Comprehensive Journal of Science, 2026)
This study aimed to identify the distinguishing characteristics of academically gifted pupils by examining the level of these characteristics and their relationship with gender, as well as analytical, creative, and practical abilities among primary school students. The descriptive correlational method was adopted as the most appropriate approach for examining relationships among variables. The study sample consisted of (108) male and female pupils from the first three grades of primary schools in Sayyad/Janzour during the academic year 2025–2026. The sample was selected using a purposive sampling method. A questionnaire directed to teachers was used as the main research instrument. It included three major dimensions: analytical ability, creative ability, and practical ability, each containing several items measuring behavioral and cognitive traits associated with academically gifted pupils. Data were analyzed using the Statistical Package for Social Sciences (SPSS), employing means, standard deviations, and the independent samples t-test, the results revealed that the overall level of the distinguishing characteristic among academically gifted pupils was relatively low compared with the established cutoff score of the measurement scale. Furthermore, the findings indicated no statistically significant differences at the significance level (0.05) between males and females in analytical, creative, and practical abilities. This suggests that gifted pupils share similar cognitive and behavioral characteristics regardless of gender, the study recommended early identification of academically gifted pupils and the development of specialized educational programs to support and enhance their abilities. It also emphasized the importance of teacher training in recognizing gifted characteristics, establishing specialized databases for gifted students, and providing supportive educational environments that foster analytical, creative, and practical skills to promote educational and societal development.